Immediate ROI Search for 3D Medical Images - Simonyan, K.; Modat, M.; Ourselin, S.; Criminisi, A.; Zisserman, A.; Criminisi, Antonio (MICCAI workshop on Medical Content-based Retrieval for Clinical Decision Support (MCBR-CDS), 2012)
The objective of this work is a scalable, real-time, visual search engine for 3-D medical images, where a user is able to select a query Region Of Interest (ROI) and automatically detect the corresponding regions within all returned images. We make three contributions: (i) we show that with appropriate oﬀ-line processing, images can be retrieved and ROIs registered in real time; (ii) we propose and evaluate a number of scalable exemplar-based image registration schemes; (iii) we propose a discriminative method for learning to rank the returned images based on the content of the ROI. The retrieval system is demonstrated on MRI data from the ADNI dataset [9], and it is shown that the learnt ranking function outperforms the baseline.